Do the Transmissible Liability Index (TLI) and Adolescent Cannabis Use Predict Paranoid and Schizotypal Symptoms at Young Adulthood?. (10th November 2021) - Sharma, Pravesh; Riehm, Kira E.; Young, Andrea S.; Reynolds, Maureen D.; Tarter, Ralph E.; Horner, Michelle S.; Hammond, Christopher J.
Abstract: Background : Adolescent cannabis use is an established risk factor for the development of psychosis, but the premorbid vulnerability factors and specificity versus generality of the psychotic symptom domains affected in cannabis-psychosis relationships remain incompletely understood. To improve our understanding of these relationships, we used longitudinal data to examine the individual and interactive effects of preadolescent transmissible liability to substance use disorders (SUD), measured via the transmissible liability index (TLI), and adolescent cannabis use on the development of two distinct psychotic symptom domains, paranoid and schizotypal personality traits in young adulthood. Methods: We performed secondary analysis of data from the Center for Education and Drug Abuse (CEDAR) study, which longitudinally assessed offspring of men with ( N = 211) and without ( N = 237) lifetime history of SUD at ages 10-12, and across adolescence as they transitioned to young adulthood. TLI scores were calculated at age 10-12, self-reported cannabis use was assessed at age 16, and paranoid and schizotypal symptoms were assessed at age 19. Results: Cannabis use at age 16 and family history of SUD were significantly associated with paranoid and schizotypal symptoms at age 19, but TLI scores were not. The interactive effect of TLI x cannabis use was also not significant. Paranoid and schizotypal symptoms showed different dose-dependent sensitivities to cannabis exposure at age 16. Conclusions: These findings indicate that adolescent cannabis use and family history of SUD differentially contribute to the development of paranoid and schizotypal personality traits through mechanisms that do not include behavioral disinhibition.